COVID-19 Crisis Management: Lessons From the United Arab Emirates Leaders - Abbas Zaher, Walid; Ahamed, Faheem; Ganesan, Subhashini; Warren, Katherine; Koshy, Ashish (Frontiers in Public Health, 2021)
This study analyses the UAE leadership’s approach in response to the COVID-19 crisis through the Organization for Economic Co-operation and Development’s Strategic Crisis Management Framework. This framework analyses the crisis management in three phases: the preparedness, response to mitigate damage and through the feedback mechanism after the crisis. The analysis showed that the key components of the UAE’s crisis management included efficient and able governance, public-private partnership and the global workforce of excellence. As a result, the UAE now ranks among the top 10 countries for its leadership and proactive approach during the COVID-19 pandemic according to Global Response to Infectious Diseases Index. The SWOT analysis on the response towards COVID-19 crisis management helped in critically analyzing and understanding the UAE’s unified and systematic response to the pandemic which provides developing and developed countries alike a new high standard for leadership and effective public health management.